Cycling in the heat - Périard, J. D.; Racinais, S. (Heat stress in sport and exercise. Thermophysiology of health and performance, 2019)
The sport of cycling involves many sub-disciplines (e.g. road and mountain) incorporating different events (e.g. road racing, time trialling, cross-country). When undertaken in the heat, performance in endurance events is progressively impaired relative to temperate conditions, whereas sprint performance may be improved in the absence of marked hyperthermia. Several pathways mediate these adjustments in performance and will be discussed in this chapter. The role of thermal strain will also be discussed as it pertains to exertional heat illness, along with countermeasures to minimise its risk and optimise performance. Differences between cycling in a laboratory and in the field will also be addressed and contextualised.